Pain management in cat - KAZAKOS (Γ.Μ. ΚΑΖΑΚΟΣ), G. M.; SAVVAS (Ι. ΣΑΒΒΑΣ), I.; RAPTOPOULOS (Δ. ΡΑΠΤΟΠΟΥΛΟΣ), D. (Journal of the Hellenic Veterinary Medical Society, 2017)
Although cats are very popular pets, pain in this species is often underestimated. The reasons for this may include difficulties in pain recognition, unfamiliarity with the use of opioids or non-steroidal analgesic drugs, and with the application of local analgesic techniques. Proper pain management should always be undertaken mainly for medical and humane purposes. Pre-emptive and multimodal analgesia can aid significanly in postoperative pain alleviation. Nowadays, the veterinarian's armamentarium is equipped with a variety of agents in order to alleviate pain in cats. Non-steroidal anti-inflammatory drugs are often as effective as opioids. The latter are now used successfully for pain management in cats. Both classes provide safe analgesia, taking into account the differences in metabolism between cats and other species. Adjunctive analgesic therapy may be provided with the use of ketamine or a2-adrenergic receptor agonists. Loco-regional analgesic techniques can be used to effectively manage pain in a variety of clinical settings.